2020
DOI: 10.13080/z-a.2020.107.037
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of organic carbon, its forms and macroelements in agricultural soils

Abstract: The objective of the present study was to estimate the distribution of soil organic carbon (SOC) and its forms (protected and labile organic carbon) and total nitrogen (N tot), plant available phosphorus (P 2 O 5) and pottassium (K 2 O) within 0-30 cm layer of a ploughed horizon in agricultural soils as influenced by tillage and fertilisation. Research was carried out in two regions of Lithuania: in Central (sites I and II) and Northern (site III) parts of Middle Lithuanian Lowland. Tillage systems, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Our data show that the significantly higher SOC concentration in the investigated soil layer (0-30 cm) occurred in the treatment fertilized with 170 N rate of both digestates, and only a tendency of increasing SOC concentration was evident under other rates of fertilization (Table 6, Figure 3). It should be noted that the study year and soil layer also influenced the SOC content [50]. In previous studies, LD and SD had different effects on non-fertile soil [4,11].…”
Section: Soil Organic Carbon (Soc)mentioning
confidence: 97%
“…Our data show that the significantly higher SOC concentration in the investigated soil layer (0-30 cm) occurred in the treatment fertilized with 170 N rate of both digestates, and only a tendency of increasing SOC concentration was evident under other rates of fertilization (Table 6, Figure 3). It should be noted that the study year and soil layer also influenced the SOC content [50]. In previous studies, LD and SD had different effects on non-fertile soil [4,11].…”
Section: Soil Organic Carbon (Soc)mentioning
confidence: 97%
“…High soil aggregation is a significant soil quality parameter since it increases porosity, and therefore increases infiltration and water-holding capacity, and reduces erosion and runoff [ 24 ]. It is also known that soil aggregates stability increases with soil organic matter content and that soil management practices such as reduced tillage, crop residues and organic fertilizers can improve soil quality [ 25 ]. SOC, N total and P total had a positive effect on the formation of water-stable aggregates in different tillage [ 7 ].…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
“…The data of Lithuanian colleagues showed that C transformation in the soil and chemical composition of the soil reflect this transformation, depending on soil management applied and the inherent properties of the soil itself. SOC has been increasingly considered as a key indicator of soil quality [ 25 ]. Literature sources claim that different types of clover–grass swards promoted SOC immobilization in microbial biomass and, at the same time, stabilized the sward ecosystem in the topsoil layer (soil respiration in 0–10 and 10–20 cm layers were lower) more effectively than the lucerne–grass sward [ 29 ].…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…In respective aspects, about 100 mL of the sample was placed in a conical flask along with 5 mL of chromous mixture (consisting of 0.2 M potassium dichromate within (1:1) dil. H 2 SO 4 ) following standard protocols [18][19][20]. A thermostat was used to facilitate the lowering of temperature.…”
Section: Determination Of Conc Of Different Soil Gasesmentioning
confidence: 99%